Implementation of Religious Moderation Values in Islamic Religious Higher Education in Garut, West Java - Ainissyifa, Hilda; Nasrullah, Yufi Mohammad (Ulumuna, 2025)
This study aims to analyze the implementation of religious moderation values in Islamic religious higher education in Garut, West Java. The primary focus of the research includes the integration of religious moderation values in the curriculum, the role of lecturers and education staff, student perceptions, as well as obstacles and challenges in implementing these values. Through a qualitative approach, data were collected through in-depth interviews, observations, and document analysis at several institutions, including STAI Musadaddiyah, STAI Muhammadiyah Garut, and STAI Siliwangi Garut. The results show that religious moderation is integrated through an Aswaja-based curriculum approach and rahmatan lil 'alamin, with lecturers and education personnel playing the role of facilitators in building tolerant and inclusive student characters. The main obstacles come from the influence of conservative ideologies, limited religious understanding among students, and challenges from social media. Strategies to overcome these obstacles include strengthening the curriculum, digital literacy training, and collaboration with external institutions. The findings are expected to make a positive contribution to the formation of a moderate generation that can apply the values of tolerance and inclusiveness in religious and social life.